Maximizing zearalenone removal: Unveiling the superior efficiency of pre-treated carbon in adsorption and photocatalysis - J.C. Gómez-Vilchis; G. García-Rosales; L.C. Longoria-Gándara; E.O. Pérez-Gómez; D. Tenorio-Castilleros (Heliyon, 2025)
Zearalenone (ZEN) is a mycotoxin produced by Fusarium species, commonly found in food, feed, and water bodies. Due to its classification as a carcinogen, ZEN is a hazardous contaminant that requires removal from aqueous and food-related effluents. To prevent its release into aquatic systems, effective tertiary treatment methods are essential. This study investigates the removal of ZEN using two advanced water treatment technologies: adsorption and photocatalysis. Two carbonaceous materials derived from avocado seed residues (BC and BCA) were synthesized and characterized using SEM, BET, and XPS techniques. The adsorption capacity of BC was determined to be 60.23 μg g⁻1, while BCA exhibited a capacity of 64.96 μg g⁻1, as modeled by the Freundlich isotherm. Both materials achieved ZEN removal efficiencies of 65 ± 5 % for BC and 70 ± 5 % for BCA, influenced by pH, temperature, and initial concentration. Photodegradation results showed removal efficiencies of 95 ± 0.68 % for BC and 98 ± 0.36 % for BCA, highlighting the critical role of light intensity in ZEN degradation. This study underscores the potential of BC and BCA for ZEN removal through advanced water treatment technologies, representing a significant step towards sustainable and environmentally friendly remediation. Furthermore, the adsorption process demonstrated reusability over 17 cycles, while the photocatalytic process showed promise for long-term and sustainable use, with up to 20 reuse cycles.